Determinan Purchase Intention Throught Brand Trust A Moderate Variabel Islamic Bussiness Ethic - Eliya Ariyanti; Ersi Sisdianto; Is Susanto (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the influence of customer satisfaction, attitude toward the product, and customer experience on purchase intention, with brand trust as a moderating variable, particularly within the context of Islamic business practices. The research highlights how consumer psychology and brand relationships interact in shaping purchasing behavior in halal markets. Methodology: A quantitative approach with a descriptive design was adopted. Primary data were collected through structured questionnaires and analyzed using the SmartPLS software, employing Partial Least Squares for structural equation modeling (SEM). This method was chosen for its ability to test complex relationships among multiple constructs simultaneously and to assess moderating effects. Results: The findings reveal that customer satisfaction and customer experience significantly influence purchase intention, whereas attitude toward the product does not exert a meaningful effect. Furthermore, brand trust moderates the relationship between customer satisfaction and purchase intention as well as between customer experience and purchase intention, but it does not moderate the link between product attitude and purchase intention. Conclusion: Customer satisfaction and experience emerge as strong predictors of purchase intention in Islamic business settings. Brand trust enhances these effects, reinforcing its role as a critical driver in halal marketing strategies. Limitations: The study is constrained by its limited sample and reliance on self-reported responses, which may reduce generalizability. Contribution: The research provides theoretical and practical insights by emphasizing the moderating role of brand trust, offering guidance for managers and policymakers to strengthen halal brand strategies.